A Comprehensive Literature Review on English Vowels - Yani Lubis; Ade Suriyani Nasution; Liyundzira Fikroh Gani (Pusat Riset dan Inovasi Nasional, 2023)
This literature review provides a comprehensive examination of English vowels, their definition, pedagogical approaches for teaching them, and the benefits of learning them. The analysis explores that there are front vowel, central vowel, and back vowel. This research identifies the effectiveness of explicit instruction, auditory training, and visual aids in improving learners' pronunciation and perception of English vowels. Understanding and mastering English vowels contribute to enhanced pronunciation, listening skills, speaking fluency, reading ability, and overall language acquisition. Furthermore, learning English vowels promotes cultural integration and facilitates cross-cultural communication. The findings from this review offer valuable insights for language educators in designing effective instructional strategies for teaching English vowels and empowering learners to excel in English-speaking environments.